Intestinal health and microbiota in salmonids: the impact of probiotics under potentially stressful conditions ... - Jaramillo Torres, Hugo Alexander (University of Plymouth, 2017)
The intestine and associated bacterial microbiota have a central role the physiology and homoeostasis of the host. The understanding of how farming conditions affect the intestine and associated microbiota of fish is the high importance to counteract the potential threats to health and welfare. Thus, this thesis aims to understand the role of stressful husbandry conditions on the intestine and associated microbiota of rainbow trout and Atlantic salmon. Within this context, the role of Pediococcus acidilactici as health promoter was also investigated Chapter 3 investigated the replacement of fishmeal by different plant protein ingredients in rainbow trout. The results of this chapter revealed that the effect of P. acidilactici on the microbiota of distal intestine in rainbow trout was dependent on the ingredients of the diet. The results also showed that the FM substitution induced major changes in the intestinal microbiota. Moreover, the modulation induced by plant-based diets on the microbiota varied ...